Pembuatan Papan Partikel (Particle Board) dari Tandan Kosong Sawit dengan Perekat Kulit Akasia dan Gambir - Fathanah, Umi; Sofyana, Sofyana (Chemical Engineering Department, Syiah Kuala University, Banda Aceh, Indonesia, 2013)
The need of wood as one of raw materials in furniture industry keeps increasing. One of efforts to reduce wood consumption is to develop research by creating composite design from material that contains sellulose to be particle board. Particle board is one of material alternatives that can be wood substitute. The objective of this research is to investigate the effect of natural-adhesive-mixture composition (acacia bark and gambier) with oil-palm-empty bunch toward mechanical property of particle board. Characterization of particle board was carried out by undertaking mechanical property testing (tensile strength and compressive strength) under wet and dry conditions. Composition variations of adhesive and oil-palm-empty bunch were 30:70; 40:60; 50:50; 60:40; 70:30. Making process of particle board is carried out by mixing oil-palm-empty bunch and adhesive with addition of 2% para-formaldehyde and water as much of 10%. Furthermore, the mixture is compressed by using Hot Press at temperature of 150oC and pressure of 10 kg/cm2 for 15 minutes. The research result indicates that the higher the adhesive composition (either adhesives of acacia bark or gambier), particle board resulted is better. In dry condition, values of the tensile strength of particle boards that have acacia bark adhesive and gambier adhesive have range of 84.2 - 104 Kgf/cm2 and 83.4 - 81.5 kg/cm2, respectively. Whereas, values of compressive strength of particle boards that have adhesives of acacia bark and gambier are in the range of 6.8 - 10.5 kg/cm2 and 6.3 - 9.3 kg/cm2, respectively. The values of tensile strength and compressive strength are obtained on compositions of adhesive: oil-palm-empty bunch 40:60, and they have fulfilled satandard of SNI 03-2105-1996. The values of tensile strength and compressive strength of particle board in wet condition, either adhesives of acacia bark or gambier, have not fulfilled standard of SNI 03-2105-1996.Keywords: empty-bunch-oil palm, acacia bark, gambier, particle board, tensile strength